Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Võ Quốc

tìm x :(x-4)x-(x-3)^2=0

 

nguyễn thị hương giang
1 tháng 11 2021 lúc 15:03

\(\left(x-4\right)x-\left(x-3\right)^2=0\)

\(\Rightarrow x^2-4x-\left(x^2-6x+9\right)=0\)

\(\Rightarrow2x-9=0\Rightarrow x=\dfrac{9}{2}\)


Các câu hỏi tương tự
Trịnh Thành Long
Xem chi tiết
Xem chi tiết
Hiếu Tuấn
Xem chi tiết
giúp mik với
Xem chi tiết
Nguyễn Thị Chuyên
Xem chi tiết
Nguyễn Thành Nam
Xem chi tiết
Ẩn danh
Xem chi tiết
Trần Ngọc Mỹ
Xem chi tiết
minh chứng 1
Xem chi tiết
Trần văn ổi
Xem chi tiết